Does Fiscal Policy Affect Economic Growth in Nigeria? - Oluwayemisi, Betty Alli-Momoh; Oladele, Rotimi; Oladipo, Olaniyan Niyi; Afolabi, Babatunde; Timilehin, Samuel Adesanya (Acta Universitatis Danubius. Œconomica, 2024)
This study examined the impact of fiscal policy on Nigeria's economic growth from 1981 to 2022, covering a 41-year period. The research investigated the effects of government recurrent expenditure, government capital expenditure, and tax revenue on Gross Domestic Product (GDP), a proxy for economic growth. Using secondary data from reputable sources, the study employs an ex-post facto research design and purposive sampling technique to analyze the relationship between fiscal policy and economic growth. The findings revealed a complex relationship between government expenditures, tax policies, and economic growth outcomes in Nigeria. Contrary to expectations, government recurrent expenditure had a positive effect on economic growth, while government capital expenditure had a negative effect. Tax revenue also had a negative effect on economic growth. These findings have significant implications for policymakers, researchers, and stakeholders interested in understanding the impact of fiscal policy on economic growth in Nigeria. The study contributes to the existing body of knowledge on fiscal policy and economic growth, providing actionable insights for data-driven policy decisions to foster sustained economic growth, development, and prosperity in Nigeria.